If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = 9x + 26 Reorder the terms: 8 + 3x = 9x + 26 Reorder the terms: 8 + 3x = 26 + 9x Solving 8 + 3x = 26 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 8 + 3x + -9x = 26 + 9x + -9x Combine like terms: 3x + -9x = -6x 8 + -6x = 26 + 9x + -9x Combine like terms: 9x + -9x = 0 8 + -6x = 26 + 0 8 + -6x = 26 Add '-8' to each side of the equation. 8 + -8 + -6x = 26 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 26 + -8 -6x = 26 + -8 Combine like terms: 26 + -8 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| 2a+3a-3=17 | | C^2+8c+48= | | b^2-8b-16=0 | | 7+5+(2x-3)= | | 3x+4x-9=12 | | x+6x-78=97 | | 8t^2-56t+80=0 | | 2x+4=2x+x+3 | | x-31/4=21/5 | | 2x^3+3x^3+(-6x^3)= | | 2x^2-x=100 | | (2x+110)+2x=300 | | 1/2y≤-7 | | 10x^3-1250=0 | | (x-4)(x-3)(x-2+3i)(x+2+3i)=0 | | 2(2x+110)+2x=300 | | 2(x+3)+5x= | | 2y=-7x+12 | | (2x+17)=(8x-13) | | X^3-8x^2=-12x | | 11n-6-10n-1=8 | | (X+5)=14 | | 6x-2x-25=31 | | 6x-2x-25=32 | | d/3-10=2 | | x^2+9x-54=0equation | | 231=-7(-4n-1) | | 2y-20=180 | | K+14=19 | | 2x-6=10.5 | | (3x-2)(x-8)=0 | | k/7=9/7 |